223k views
1 vote
Solve each system of the equation by elimination. y=4x-15y=-2x-3

User Sach
by
6.2k points

1 Answer

5 votes

y=4x-15 (a)

y=-2x-3​ (b)

First, multiply (b) by 2 and add both equations

y = 4x -15

+

2y = -4x -6

___________

3y= -21

y= -21/3

y= -7

Replace y on any initial equation, and solve for x

-7 = 4x-15

-7+15 = 4x

8 = 4x

8/4 = x

x = 2

User Countryroadscat
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.